Production of Alkyl Levulinates from Carbohydrate-Derived Chemical Intermediates Using Phosphotungstic Acid Supported on Humin-Derived Activated Carbon (PTA/HAC) as a Recyclable Heterogeneous Acid Catalyst - Nivedha Vinod; Saikat Dutta (Chemistry, 2023)
This work reports a straightforward and high-yielding synthesis of alkyl levulinates (ALs), a class of promising biofuel, renewable solvent, and chemical feedstock of renewable origin. ALs were prepared by the acid-catalyzed esterification of levulinic acid (LA) and by the alcoholysis of carbohydrate-derived chemical platforms, such as furfuryl alcohol (FAL) and α-angelica lactone (α-AGL). Phosphotungstic acid (PTA) was chosen as the solid acid catalyst for the transformation, which was heterogenized on humin-derived activated carbon (HAC) for superior recyclability. Using HAC as catalyst support expands the scope of valorizing humin, a complex furanic resin produced inevitably as a side product (often considered waste) during the acid-catalyzed hydrolysis/dehydration of sugars and polymeric carbohydrates. Under optimized conditions (150 °C, 7 h, 25 wt.% of 20%PTA/HAC-600 catalyst), ethyl levulinate (EL) was obtained in an 85% isolated yield starting from FAL. Using the general synthetic protocol, EL was isolated in 88% and 84% yields from LA and α-AGL, respectively. The 20%PTA/HAC-600 catalyst was successfully recovered from the reaction mixture and recycled for five cycles. A marginal loss in the yield of ALs was observed in consecutive catalytic cycles due to partial leaching of PTA from the HAC support.